2015
DOI: 10.1039/c4cy01435a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of catalytically active CeO2 for soot combustion

Abstract: Pure ceria catalysts were prepared by a facile modified homogeneous co-precipitation method, and their catalytic performance was evaluated in the soot oxidation reaction. The structure and textural properties of the synthesized catalysts were characterized via XRD, N 2 adsorption/desorption, TG-DSC-MS, H 2 -TPR, FE-SEM, HR-TEM and XPS techniques. It is shown that CeO 2 samples prepared by the improved co-precipitation method exhibit obviously better catalytic activity than those prepared by the conventional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…The presence of all these peaks clearly indicate the coexistence of Ce 4+ and Ce 3+ ions on the surface of all samples. More importantly, it is reported that the existence of Ce 3+ in doped ceria based catalysts is generally associated with the formation of oxygen vacancies, and higher concentration of Ce 3+ implies larger amounts of oxygen vacancies [31]. The relative Ce 3+ concentration can be determined by the ratio: Ce 3+ /(Ce 4+ + Ce 3+ ), where Ce 4+ and Ce 3+ represent the sums of the spectral peak areas related to the Ce 4+ and Ce 3+ , respectively [32].…”
Section: Xps H 2 -Tpr and Osc Measurementsmentioning
confidence: 99%
“…The presence of all these peaks clearly indicate the coexistence of Ce 4+ and Ce 3+ ions on the surface of all samples. More importantly, it is reported that the existence of Ce 3+ in doped ceria based catalysts is generally associated with the formation of oxygen vacancies, and higher concentration of Ce 3+ implies larger amounts of oxygen vacancies [31]. The relative Ce 3+ concentration can be determined by the ratio: Ce 3+ /(Ce 4+ + Ce 3+ ), where Ce 4+ and Ce 3+ represent the sums of the spectral peak areas related to the Ce 4+ and Ce 3+ , respectively [32].…”
Section: Xps H 2 -Tpr and Osc Measurementsmentioning
confidence: 99%
“…Here, three kinds of surface oxygen species were identified. The peak with binding energy at 531.1-531.3 eV can be attributed to the defect oxide or the surface oxygen ions with low coordination and weakly-bonded oxygen species (O ads ) adsorbed on oxygen vacancies, and the peak with binding energy at 532.3-532.7 eV is assigned to adsorbed oxygen species from hydroxyl and adsorbed water species (O w ) on the surface [38,40]. The peak with binding energy at 529.1-529.5 eV was ascribed to lattice oxygen (O latt ) [23].…”
Section: Xps Studiesmentioning
confidence: 99%
“…In Ref. [90] the catalytic activity of pure ceria prepared by co-precipitation method was described. Precipitation of aqueous solution of HNO 3 and Ce(NO 3 ) 3 was carried out using the 0.4 M NaOH solution and 0.4 M Na 2 CO 3 .…”
Section: Soot Oxidationmentioning
confidence: 99%